Dragon Machine Language for the Absolute Beginner - Reyden, John (Retro Reproductions, 2022)
First published in 1983, this easy-to-follow guide to using machine language on the Dragon 32 gave users an excellent insight into the acclaimed machine that many considered well ahead of its time. Though it was more powerful and quicker than many of its competitors, the Dragon 32 never gained the success of other 8-bit computers of the day such as the Commodore 64 or the ZX Spectrum. Despite this, the classic machine still retains a dedicated following to this day. Not only is this remastered version perfect for hobbyists and collectors, it is also a highly useful resource for those interested in programming retro games and utilities.* * *As the original publisher Melbourne House wrote:Write faster, more powerful space saving programs for your Dragon.Written exclusively for Dragon users, Dragon Machine Language for the Absolute Beginner offers a complete instruction course in 6809 Machine Language, with particular reference to the Dragon 32.Even with no previous experien.